A multi-function desalination system based on hydrolysis reaction of hydride and fuel cell water recovery. (1st November 2021) - Yao, Jing; Guo, Leilei; Zhu, Pengfei; Yang, Fusheng; Yan, Hongli; Kurko, Sandra; Yartys, Volodymyr A.; Zhang, Zaoxiao; Wu, Zhen
Graphical abstract: Highlights: Multi-function desalination system with fresh water, electric and cold energy is proposed. Lumped model of this system is developed to describe the heat and mass transfer. Unit power consumption of the system can be lower to about 880W h/kg. The system is applicable for remote coastal area due to its flexibility and multi-function. Abstract: Desalination is an important method to take full advantage of the sea water to produce fresh water. However, the systems or devices reported previously still have the limitations in the energy supply and portability when used in some specific application scenarios, such as island and remote coastal area. In this paper, a multi-function desalination system is proposed, which could provide fresh water, electrical energy, and even the cold energy based on the hydrolysis reaction of hydride and fuel cell water recovery. Besides, the system could be modified to increase the flexibility of the system operation to satisfy the various energy demands under different conditions. A lumped parameter model of the proposed system is developed to evaluate the system performance. The results show that the fuel cell helps to increase the absolute humidity of the wet air by 15.5% and to increase the water production by condensing the wet air by 1.8 times compared with simple water harvest from the ambient environment. The modified system demonstrates more stable performance of the water production than the original desalination system, which means that the modified system is less affected by the parameter variation. The maximum water production of the kW level system could achieve 11.10 kg/h. Comparing with the previous reports, the unit power consumption of the modified system could reach the lowest level (about 880 Wh/kg), showing the promising water production performance of the system developed in this work.